Serious gaming: implications for resilience governance of critical infrastructure. (4th October 2019) - Jules-Plag, Shelley; Vasuthanasub, Jarutpong; Gheorghe, Adrian
Risk and risk governance of critical infrastructure has been well studied. Resilience governance however is still in the process of identifying suitable approaches. Assessments of resilience are often based on value perspectives and impacted by social constructs, making it difficult to fit a singular approach to resilience governance, creating wicked problems for decision makers. The paper looks at the steps utilised in risk informed decision making (RIDM) and their applicability to resilience informed decision making (ReIDM), identifying benefits and limitations. It proposes a framework to address the process-oriented approach needed for ReIDM. To demonstrate the framework we utilise a number of risk assessment methodologies, and a simple time-dependent game play simulation SimCity™ model to explore the manifestation of infrastructure development strategies over time, illustrating the importance of tools that facilitate insight into the domino effects of alternative approaches and mitigation strategies to resilience governance.